Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 325865 species occurrences available in GBIF matching the query: { "Country" : [ "is Ethiopia" ] } The dataset includes 325865 records from 364 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0013962-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences